Plasma apolipopotein C-2 elevation is associated with Takayasu arteritis - Natsuko Tamura (Nature Portfolio, 2021)
Abstract Takayasu arteritis (TAK) is an autoimmune systemic arteritis of unknown etiology. Although a number of investigators have attempted to determine biomarkers for diagnosing TAK, there exist no specific serological markers of this intractable disease. We undertook the exploration of novel serological markers which could be useful for an accurate diagnosis of TAK using an unbiased proteomics approach. The purified plasma samples from untreated patients with TAK and healthy individuals were separated by two-dimensional electrophoresis. The differentially expressed protein spots were detected by gel comparison and identified using matrix-assisted laser desorption/ionization time-of-flight/time-of-flight mass spectrometry (MS). Next, we validated plasma concentrations of identified proteins by enzyme-linked immunosorbent assay (ELISA). Two-dimensional electrophoresis and numerical analysis revealed 19 spots and 3 spot clusters whose sum of the sample averages was ≥ 0.01, and the average concentrations were ≥ 1.5 times in the patient group compared with the control group. Among them, 10 spots and spot clusters that met the condition of the average spot concentration being 2.5 times more than that in the control group were selected. After processing these spots using MS and conducting MS/MS ion search, we identified 10 proteins: apolipoprotein C-2 (ApoC-2), actin, apolipoprotein A-1, complement C3, kininogen-1, vitronectin, α2-macroglobulin, 14–3–3 protein ζ/δ, complement C4, and inter-α-trypsin inhibitor heavy chain H4 isoform 1 precursor. Finally, ELISA demonstrated that plasma ApoC-2 level was significantly elevated in patients with TAK compared with that in healthy individuals. Thus, ApoC-2 would be a promising candidate biomarker for TAK diagnosis.